Apex Omnium Religion in the Res Gestae of Ammianus. - Rike, R. L. (Transformation of the Classical Heritage Series., 2021)
One of the masterpieces of Greco-Roman literature is the history written by Ammianus Marcellinus near the end of the fourth century A.D. His work bears unique witness to an empire struggling at once toward traditional and transformation, the old Rome of Augustus and the new Rome of Christ. Embodied within Ammianus's history is a universally admired spirit of independence that has, however, led to a steady denaturing of the historian's personal commitment to pa.